Letter - West Ham Trades Council and Borough Labour Party, 4 May 1926 (West Ham)
1926-05-04 "Letter - West Ham Trades Council and Borough Labour Party, 4 May 1926" [g0247001.jpg], 4 May 1926 Local Organisation